Aspergillus fumigatus Inhibits Pseudomonas aeruginosa in Co-culture: Implications of a Mutually Antagonistic Relationship on Virulence and Inflammation in the CF Airway - Reece, Emma; Doyle, Sean; Greally, Peter; Renwick, Julie; McClean, Siobhán (Frontiers in Microbiology, 2018)
Many cystic fibrosis (CF) airway infections are considered to be polymicrobial and microbe-microbe interactions may play an important role in disease pathology. Pseudomonas aeruginosa and Aspergillus fumigatus are the most prevalent bacterial and fungal pathogens isolated from the CF airway, respectively. We have previously shown that patients co-colonised with these pathogens had comparable outcomes to those chronically colonised with P. aeruginosa. Our objective was to examine the interactions between A. fumigatus and P. aeruginosa, specifically the effects of co-colonisation on biofilm formation, virulence and host pro-inflammatory responses. Our findings suggest that co-infections of A. fumigatus and P. aeruginosa in the Galleria mellonella acute infection model showed that pre-exposure of larvae to sub-lethal inocula of A. fumigatus increased the mortality caused by subsequent P. aeruginosa infection. Co-infection of human bronchial epithelial cells (CFBE41o-) with both pathogens did not enhance IL-6 and IL-8 production beyond the levels observed following single infections. In addition, both pathogens stimulated cytokine secretion via the same two mitogen-activated protein kinases (MAPK) signalling pathways, ERK and p38. Mixed species biofilms showed overall reduced biofilm development with crystal violet staining. Quantification by species-specific qPCR revealed that both pathogens had mutually antagonistic effects on each other. A. fumigatus supernatants showed strong anti-Pseudomonal activity and gliotoxin was the main active agent. Gliotoxin resulted in varying levels of anti-biofilm activity towards other bacteria commonly found in the CF airways. Gliotoxin produced by A. fumigatus colonising the CF airways may have a significant impact on the CF airway microbiome composition with potential clinical implications.